2019
DOI: 10.1039/c9cc06868f
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan–glucosamine conjugates modulate tau-derived PHF6 aggregation at low concentrations

Abstract: Tryptophan–glucosamine conjugates efficiently inhibit tau-derived PHF6-peptide fibrillization and disrupt its preformed fibrils at very low concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…To begin with, we first evaluated the effects of Trp‐glucose conjugates on Aβ aggregation . It was reported that tryptophan derived molecules could inhibit the aggregation of some amyloid proteins, including Aβ .…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…To begin with, we first evaluated the effects of Trp‐glucose conjugates on Aβ aggregation . It was reported that tryptophan derived molecules could inhibit the aggregation of some amyloid proteins, including Aβ .…”
Section: Methodssupporting
confidence: 91%
“…Thus, we looked forward to achieving a better inhibitory effect by covalently linking Trp and glucose. As previously described, we successfully got the Trp‐glucose conjugates ASn ( n =1,2,3. Scheme ).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…The conjugation of glycans to peptides increases the overall interaction surface of the hybrid molecules, therefore increasing solubility by expanding the number of possible interactions with the solvent 50 53 . Along the same rationale, aromatic molecules, which display high potential as anti-amyloidogenic agents, but are by themselves hydrophobic, were conjugated to mannitol and glucosamine 43 , 54 .…”
Section: Introductionmentioning
confidence: 99%